2020
DOI: 10.1590/0100-29452020099
|View full text |Cite
|
Sign up to set email alerts
|

Active modified atmosphere storage to preserve the quality of 'San Andreas' strawberries harvest at two ripening stages

Abstract: This work was carried out to evaluate the effect of fruit ripening stage at harvest (“1/3 ripe” and “3/4 ripe”, respectively with 30% and 75% of red color) and passive modified atmosphere (MA) and active MA (with initial initial low O2 and/or high CO2) on quality of ‘San Andreas’ strawberries, with emphasis on bioactive compounds and metabolites of fermentative metabolism. The treatments evaluated were: control; passive MA [low density polyethylene (LDPE) packaging of 40 µm]; active MA with initial low O2 (1 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The volatile alcohols were also mostly suppressed in TTEOtreated fruits, except for ethanol that was found only in fruits treated with 300 and 600 μl L −1 of the TTEO (Table 3). Anami et al (2020) found that fruits in an advanced ripening stage contained a higher concentration of ethanol, indicating fermentative metabolism.…”
Section: Re Sults and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The volatile alcohols were also mostly suppressed in TTEOtreated fruits, except for ethanol that was found only in fruits treated with 300 and 600 μl L −1 of the TTEO (Table 3). Anami et al (2020) found that fruits in an advanced ripening stage contained a higher concentration of ethanol, indicating fermentative metabolism.…”
Section: Re Sults and Discussionmentioning
confidence: 94%
“…Anami et al. (2020) found that fruits in an advanced ripening stage contained a higher concentration of ethanol, indicating fermentative metabolism. Ethanol is one of the compounds responsible for off flavor (Yan et al., 2018), and in this case, it is probably related to the advancement in the fruit ripening process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The greasiness index was assessed according to the methodology described by Yang et al (2017a). The fermentative metabolism compounds were quantified as described by Anami et al (2020). The scald incidence (%) was visually assessed by counting the fruits with dark spots on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Although these fruits retained high values of compounds associated with antioxidant activity, particularly at 15°C, harvest at this maturity stage did not favour adequate ripening. Anami et al (2020) showed that the handling of strawberry, a non-climacteric fruit, harvested at 1/3 ripe condition, allowed the antioxidant potential to have higher values, but colour attributes did not reach typical consumption values, as did fruits that were harvested at 3/4 ripeness. In the present work, fruits harvested at transient maturity experienced softening, thus giving them a texture similar to that of yellow fruits, and the hue angle and chroma tended toward the reference values, although lightness decreased.…”
Section: Feasibility Of Early Harvestmentioning
confidence: 99%